Combination of Oven and Microwave-assisted Drying Technique for Production of Ready-to-Eat Dried Rice - Md Lazim, Nurul Asmak; Dayang Norulfairuz (International Journal of Integrated Engineering, 2024)
A combination of oven and microwave was introduced with the purpose of preparing well-balanced dried ready-to-eat dried rice samples. The parameter condition was investigated (oven temperature; 70 and 90 °C, time; 70, 130 and 180 min, microwave power; 450 and 750 W and time; 1, 2, 3, 4 and 5 min). From the study, increasing in moisture content and rehydration capability was obtained when the drying conditions were increased. However, the color product was changing as the color difference was improved whereby the samples with lower water activity have lower microorganism growth (0.4-0.5 wa). The nutrient obtained were in the range of 55.5 - 65.9% for carbohydrate, 6.4 - 9.3% for protein, 65.9 - 17.3% for fat and 3.4 - 3.5 for ash content, respectively. It can be concluded that the use of oven and microwave in this study is acceptable for preparing ready-to-eat dried rice.